COMPARISON OF PPH IN INDUCED WITH PROSTAGLANDIN E2 VERSUS SPONTANEOUS LABOUR - JAWARIA, .; PARVEEN, S; ZUBAIR, H; FATIMA, A; AYESHA, .; AHMED, A (Biological and Clinical Sciences Research Journal, 2024)
Postpartum haemorrhage (PPH) remains a significant obstetric complication, leading to maternal morbidity and mortality. The impact of labour induction on the incidence of PPH compared to spontaneous labour is crucial for guiding clinical practices. Objective: To compare the incidence of postpartum haemorrhage in patients undergoing induced labour versus those experiencing spontaneous labour. Methods: A randomized controlled trial was conducted from April to September 2024 in the Obstetrics and Gynecology Department of DHQ Teaching Hospital, Mirpur AJK. A total of 70 patients with term singleton pregnancies were included, with 35 undergoing spontaneous labour and 35 experiencing labour induction. The incidence of PPH was recorded in both groups. Informed consent was obtained from all participants, and ethical approval was granted by the hospital’s ethics committee. Results: Among 35 patients with spontaneous labour, 88.57% (n=31) had normal vaginal deliveries, 11.43% (n=4) underwent cesarean sections, and 8.5% (n=3) experienced PPH. In contrast, of the 35 patients induced into labour, 77.14% (n=27) had normal vaginal deliveries, 22.85% (n=8) underwent cesarean sections, and 31.43% (n=8) experienced PPH. The incidence of PPH was significantly higher in the induced labour group compared to the spontaneous labour group. Conclusion: Labor induction is associated with an increased frequency of postpartum haemorrhage. Induction should be reserved for cases with strong medical indications, and safer methods, such as prostaglandins, should be preferred over artificial rupture of membranes to minimize risks.